High phenotypic diversity correlated with genomic variation across the European Batrachochytrium salamandrivorans epizootic. - Moira Kelly; Christina A Cuomo; Wouter Beukema; Salvador Carranza; Jesse Erens; Marleen Foubert; Zhimin Li; Stefan Lötters; Vanessa Schulz; Sebastian Steinfartz; Sarah Van Praet; Michael Veith; et al. (PLoS Pathogens)
Recognizing the influence of pathogen diversity on infection dynamics is crucial for mitigating emerging infectious diseases. Characterising such diversity is often complex, for instance when multiple pathogen variants exist that interact differently with the environment and host. Here, we explore genotypic and phenotypic variation of Batrachochytrium salamandrivorans (Bsal), an emerging fungal pathogen that is driving declines among an increasing number of European amphibian species. For thirteen isolates, spanning most of the known temporal and geographical Bsal range in Europe, we mapped phenotypic diversity through numerous measurements that describe varying reproductive rates in vitro across a range of temperatures. Bsal isolates are revealed to have different thermal optima and tolerances, with phenotypic variation correlating with genomic diversity. Using a mechanistic niche model of the fire salamander (Salamandra salamandra) as an example, we illustrate how host steady-state body temperature and Bsal thermal range variation may influence pathogen growth through space and time across Europe. Our combined findings show how the identity of emergent pathogen variants may strongly influence when and which host populations are most at risk.